Does time pressure affect intertemporal choice : an experimental study - Ong, Chun Keat (2014)
This paper examines whether individual's intertemporal choice is affected under time pressure. We recruited 90 subjects to participate in our laboratory experiment and asked them to answer a series of time preference questions. Time limit to complete the task was imposed on the participants in the treatment group. Our results indicate that there is no general effect of time constraint on individual's intertemporal choice. However, after disaggregating subjects according to their mood - participants that felt tensed in the treatment group were found to have higher discount rates while those that did not feel the time pressure had lower discount rates, relative to the control group. This suggests that time constraint does have an effect on subjects' intertemporal choice but it is conditional on how individual reacts to time pressure.